Long Term Warranty and After Sales Service Concept, Policies and Cost Models - Rahman, Anisur; Chattopadhyay, Gopinath; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume presents concepts, policies and cost models for various long-term warranty and maintenance contracts. It offers several numerical examples for estimating costs to both the manufacturer and consumer. Long-term warranties and maintenance contracts are becoming increasingly popular, as these types of aftersales services provide assurance to consumers that they can enjoy long, reliable service, and protect them from defects and the potentially high costs of repairs. Studying long-term warranty and service contracts is important to manufacturers and consumers alike, as offering long-term warranty and maintenance contracts produce additional costs for manufacturers / service providers over the product$1 (Bs service life. These costs must be factored into the price, or the manufacturer / dealer will incur losses instead of making a profit. On the other hand, the buyer / consumer needs to weigh the cost of maintaining it over its service life and to decide whether or not these policies are worth purchasing. There are a number of complexities involved in developing failure and cost models for these policies due to uncertainties concerning the service life, usage pattern, maintenance work and long-term costs of rectifications. Mathematical models for predicting failures and expected costs for various one-dimensional long-term warranty policies are developed at the system level and analyzed by taking into account the uncertainties in connection with longer coverage periods and the rectification costs over the warranty period. Failures and costs are modeled using stochastic techniques and illustrated by means of numerical examples for estimating costs to the manufacturer and consumer. Various rectification policies are proposed and analyzed. The models developed here can be used to aid in managerial decisions on purchasing products with long-term warranty policies and maintenance contracts or outsourcing maintenance.s
Introduction to Long-Term Warranty and After-Sales Service -- Lifetime Warranties : Policies and Cost Models -- Used Second-hand Product Warranty -- Extended Warranty -- Maintenance Contract -- Outsourcing Rail Maintenance through Maintenance Contracts - A Case Study.
Keywords: Engineering; Organization; Planning; Engineering economics; Engineering economy; Quality control; Reliability; Industrial safety; Engineering; Engineering Economics, Organization, Logistics, Marketing; Organization; Quality Control, Reliability, Safety and Risk; Electronic books